(3GdCMcGe hGdbhGYO GdELQGFjI dLQjeI ZSd GdCehGd (B:s (3OQGSI ebGQfI(B/ s - (3CMeO QGTO GdXfMGfjs; (3eOMJ YHO GdMdje QeVGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2019)
Summary: (3JfGhdJ gPg GdOQGSI GdCMcGe h GdbhGYO GdELQGFjI dLQjeI ZSd GdCehGd(B: (3h Je JbSje gPg GdOQGSI Edj HGHjf jSHbgeG aUd JegjOi(B: (3HYfhGf eGgjI LQjeI ZSd GdCehGd(B: (3h CMcGegG GdehVhYjI(B: (3h JfGhdJ ai GdHGH GdChd GdEWGQ GdELQGFi dLQjeI ZSd GdCehGd(B: (3h ai GdHGH GdKGfi GdCMcGe h GdbhGYO GdELQGFjI ai Xd GdJYGhf GdOhdi dLQjeI ZSd GdCehGd h GdbGfhfjf GdeUQi h GdEeGQGJi(B. (3h NdUJ GdOQGSI Edi fJGFL efgG(B: (3Ef LQjeI ZSd GdCehGd LQjeI JHYjI(B: (3h LQjeI YeOjI(B: (3h gi ef LQGFe GdSdhc GdeLQO(B: (3h JJeKd UhQ GdSdhc GdeGOi ai CaYGd JMhjd Ch fbd GdCehGd(B: (3Ch ENaGA Ch Jehjg MbjbI GdCehGd Ch GcJSGH Ch MjGRI Ch GSJNOGe GdCehGd(B. (3ceG Ef GdeTQYjf GdeUQi h GdEeGQGJi GYJQaG HGdeSDhdjI GdLfGFjI GdeHGTQI ddTNU GdGYJHGQi(B: (3h bO CNP GdeTQY GdeUQi hGdEeGQGJi HGdNjGQ GdEOGQj ai JMOjO GdLgI GdeNJUI HecGaMI ZSd GdCehGd(B: (3ceG Cf GdeTQY GdEeGQGJj hVY bjhOkG NGUI Ydi EbGeI GdOYhi GdLfGFjI h bO bUQgG Ydi GdfGFH GdYGe(B: (3h hVY GdJTQjY GdEeGQGJi h GdeUQi bhGYO NGUI ai GdJMaX Ydi GdCehGd GdeTJHg HgG(B: (3MjK CMGd GdeTQY GdeUQi Edi ehGO GdJMaX GdefUhU YdjgG ai bGfhf GdELQGAGJ GdLfGFjI(B: (3HjfeG MQU GdeTQY GdEeGQGJi Ydi GdfU Ydi Jdc GdbhGYO h GdJOGHjQ GdJMaXjI Ydi GdCehGd GdeTJHg HgG aj fUhU bGfhf ecGaMI ZSd GdCehGd hGddGFMI GdJfajPjI dg(B. (3ceG Cf fjGHI Gef GdOhdI GdYdjG gi GdLgI GdeNJUI HGdJMbjb GdOYhi GdLfGFjI ai LQGFe ZSd GdCehGd ai GdJTQjY GdeUQi(B: (3HjfeG GdfjGHI GdYGeI ai ecGf hbhY GdLQjeI gi GdeNJUI ai GdJTQjY GdEeGQGJi(B: (3h de jJVef GdJTQjY GdeUQi bhGYO JfXe TQhW GdJSdje h ELQGAGJg(B: (3Ydi NdGa Pdc aEf GdeTQY GdEeGQGJi hVY bhGYO h fUhU ai bGfhf ZSd GdCehGd h dGFMJg GdJfajPjI(B: (3h GdbGfhf Qbe (B39 (3dSfI (B2006 (3HTCf GdJYGhf GdbVGFi GdOhdi ai GdeSGFd GdOhdjIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFj (B2019.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 472-493 (3UaMIs
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFj GdebGQfs; (3LQjeI ZSd GdCehGds; (3GdJMbjb GdLfGFjs; (3GdJOGHjQ GdJMaXjIs; (3GdefY ef GdJUQas; (3JSdje GdeLQejfs; (3GdMce GdLfGFj GdCLfHjs; (3hMOI GdJMQjGJs; (3GdOYhi GdLfGFjIs; (3JbGOe GdOYhi GdLfGFjIs; (3JbGOe GdYbhHIs; (3ecGaMI ZSjd GdCehGds; (3Jehjd GdEQgGHs; (3GdJMaX ddeMceIs; (3GdbUO GdLfGFj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs